Experimental Magnetic and Iron Loss Degradation in Electrical Machines - Lidskog, Victor (My University, 2023)
Abstract With the automotive industry increasingly transitioning towards a fully electric fleet of vehicles, the development of highly efficient electrical machines has become a crucial undertaking. In order to achieve precise simulation outcomes during the design phase of these electrical machines, it is imperative to consider the impact of cutting the lamination steel utilized in the stator and rotor. This research work focuses on the utilization of an Epstein frame and a Single Strip Tester to evaluate the effects of cutting on the electrical steel, specifically using a laser cut technique. The study encompasses both sinusoidal and non-sinusoidal flux distributions. Magnetic property degradation and iron losses were measured and subjected to comprehensive analysis. A test sequence encompassed multiple fundamental frequencies and varied flux density levels, resulting in over 1500 individual test measurements. The outcomes of these measurements were extensively analyzed and discussed. To generate the non-sinusoidal flux, Pulse Width Modulation (PWM) was used, and the effects of altering the amplitude modulation index and frequency modulation index were measured and analyzed. The degradation of magnetic properties exhibited an exponential pattern, with the greatest degradation occurring closest to the cut edge, reaching an increase of 3.3 times as much magnetic field strength . Conversely, the degradation of iron losses exhibited a more linear increase, with the highest degradation reaching 1.5 times increase, near the cut edge. The magnitude of degradation depended on both the flux density level and the fundamental frequency, with greater degradation observed at lower frequencies and reduced degradation at saturation levels in the electrical steel. Based on the measured results, a model was developed to incorporate the degradation into a Finite Element Method (FEM) simulation model of a Permanent Magnet Synchronous Machine (PMSM). The FEM simulation was conducted at various frequencies, focusing on a single load point at half the rated current. It is important to note that the degradation resulting from non-sinusoidal flux is a highly intricate topic that necessitates further investigation. Multiple factors, including fundamental frequency, frequency modulation index, amplitude modulation index, flux density level, distance from the cut edge, and more, con tribute to the degradation, resulting in a multitude of degrees of freedom and increased complexity. The simulation outcomes indicated a decrease in torque and an increase in iron losses when compared to a non-degraded model. Consequently, the machine’s efficiency was reduced by approximately 0.5% to 2%, depending on the fundamental frequency.